Lag Screw Fixation for Treatment of an Ulnar Styloid Process Fracture with Antebrachiocarpal Joint Luxation in a Cat - Parker, Lindsay A.; Kapatkin, Amy S.; Fuller, Mark C. (VCOT Open, 2019)
Fracture of the ulnar styloid process can result in clinically debilitating antebrachiocarpal instability. Previously described repair methods include Kirschner wire and figure of eight tension band wire and/or intramedullary pinning. This case report describes surgical repair of a short oblique ulnar styloid process fracture in a cat using two cortical screws placed in lag fashion. Recheck evaluation confirmed lameness-free full return to function with anatomical fracture healing.
Keywords: feline ulnar styloid fracture; osteosynthesis